Hitler's allies : the ramifications of Nazi alliance politics in World War II - Miglietta, John P., 1962- 1962- (Routledge studies in Second World War history, 2022)
The significance of great/small power alliances -- Italy and Germany -- Germany and Japan during World War II, allies at a distance -- Hungary -- Romania -- Finland, the co-belligerent of Nazi Germany -- Vichy France, the occupied ally -- Spain, the friendly neutral -- Bulgaria, an ally at a distance -- Croatia the vassal state -- Switzerland and Sweden the armed neutrals -- The Islamic world and Nazi Germany -- Conclusion: The pitfalls of great and small power alliances